Perspectiva ocupacional da participação de crianças na educação infantil e implicações para a terapia ocupacional - Folha, Débora Ribeiro da Silva Campos (2019)
In this study, we problematize the invisibility of children's occupations, with an emphasis on Early Childhood Education. The general objective was to describe and analyze the education of children from an occupational perspective. The specific objectives were: a) To describe the activities, routines and environments of Early Childhood Education from an occupational perspective; b) To understand and analyze how children with typical and atypical development become involved in the activities, routines and environments of Early Childhood Education; and c) To identify and analyze the implications for Occupational Therapy in order to promote the participation of children in Early Childhood Education, from an occupational perspective. It was na empirical, qualitative, descriptive and exploratory research. The study participants were: four children with typical development; four children targeted by special education, three with Autism Spectrum Disorders and one with physical disability due to congenital malformation; four pre-school teachers and one trainee that accompany one of the children. Data collection was performed from direct observation according to the narrative descriptions technique. In addition, semi-structured interviews were conducted with the teachers and the trainee. The content analysis technique guided the data analysis. We found three categories of analysis: 1) Environments, routines and activities of early childhood education, which brings together results related to environments as promoters or inhibitors of participation in early childhood education, as well as analyzing the learning opportunities present in school routines, grouping the activities of early childhood education around three axes. : play, self-care and formal learning activities; 2) Participation of children with typical development and PAEE children in the environments, routines and activities of early childhood education, which presents and discusses results regarding the participation profiles in the three axes of early childhood activities found in the study, among which children with typical development predominantly demonstrated full participation and PAEE children demonstrated participation ranging from full, active assisted participation to restricted participation; and 3) Uncovering spaces for Occupational Therapy in Early Childhood Education from an occupational perspective, a category that analyzes gaps found in the results that allow contributions from Occupational Therapy to the context of Early Childhood Education. The defense for the understanding of Early Childhood Education from an occupational perspective contemplates the comprehension of the school occupations of play, self-care and learning of formal contents. Children with typical development show full participation in these occupations. Special Education Target Children, especially those who manifest Autism Spectrum Disorders, have restricted participation and require mediation. The specificity of the occupational therapist is to develop strategies to promote the full participation of all children in these occupations